PHARMACOLOGY AND CHEMOTHERAPEUTIC EFFECT OF PENSTREP 400 ON CATTLE - Rejepbayev J.E.; Gabbarova U.U. ,Zoitova S.A. (Research Focus International Scientific Journal, 2026)
This article describes the pharmacological properties of Penstrep 400 and its chemotherapeutic effect in the treatment of infectious diseases in cattle. The combination of penicillin and streptomycin antibiotics, which are part of the preparation, has a wide spectrum of action and exhibits high bactericidal effectiveness against gram-positive and gram-negative microorganisms. The absorption, distribution, and excretion of Penstrep 400 in the body, as well as its ability to maintain therapeutic concentration for a long time, were analyzed. The results of the study showed the effectiveness of the drug in the treatment of infections of the respiratory tract, digestive system, genitourinary organs, and mammary glands.